Problematika Implementasi Dasar-Dasar Kependidikan dalam Praktik Pembelajaran - Mizra Tri Hapsari; Nisatul Aulia; Gusmaneli (JURNAL ILMIAH NUSANTARA, 2026)
The fundamentals of education are a crucial theoretical and philosophical foundation for the implementation of the learning process. This concept encompasses an understanding of educational objectives, the role of teachers, student characteristics, the curriculum, and learning methods and strategies. However, in the real world, the application of the fundamentals of education often faces various challenges. This article aims to analyze the problems in applying the fundamentals of education in learning practices and identify the factors that influence them. The method used is a literature study by analyzing various sources such as books and scientific journal articles related to the field of education. The results of this study indicate that challenges in implementing the fundamentals of education arise from differences between theoretical concepts and real-life classroom situations. Some of the main problems that arise include teachers' lack of understanding of the fundamentals of education, limited pedagogical competence, lack of ability to design student-focused learning, and the influence of educational policies that tend to be administrative in nature. In addition, learning environment factors, the condition of facilities and infrastructure, and differences in student characteristics also complicate the process of maximally implementing educational concepts. The impact of these problems is low learning effectiveness and the achievement of educational goals. Therefore, efforts are needed to improve educators' understanding of the fundamentals of education through ongoing training, reflection on learning practices, and synergy between theory and practice. This is expected to make the application of the fundamentals of education more effective and relevant to current educational needs.